Phylogenetic Correlation and Symbiotic Network Explain the Interdependence Between Plants and Arbuscular Mycorrhizal Fungi in a Tibetan Alpine Meadow - Dong, Qiang; Guo, Xin; Chen, Keyu; Ren, Shijie; Muneer, Muhammad Atif; Zhang, Jing; Li, Yaoming; Ji, Baoming (Frontiers in Plant Science, 2021)
Plants and arbuscular mycorrhizal fungi (AMF) can form complex symbiotic networks based on functional trait selection, contributing to the maintenance of ecosystem biodiversity and stability. However, the selectivity of host plants on AMF and the characteristics of plant-AMF networks remain unclear in Tibetan alpine meadows. Here, we studied the AMF communities in 69 root samples from 23 plant species in a Tibetan alpine meadow using Illumina-MiSeq sequencing of 18S rRNA gene. The results showed a significant positive correlation between the phylogenetic distances of plant species and the taxonomic dissimilarity of their AMF community. The plant-AMF network was characterized by high connectance, high nestedness, anti-modularity and anti-specialization, and the phylogenetic signal from plants was stronger than that from AMF. The high connected and nested plant-AMF network potentially promoted the interdependence and stability of the plant-AMF symbioses in Tibetan alpine meadows. This study emphasizes that plant phylogeny and plant-AMF network play an important role in the coevolution of host plants and their mycorrhizal partners and enhances our understanding of the interactions between above- and belowground communities.